Las estructuras de poder y los procesos de evaluación - Peleteiro, María Concepción (Revista Española de Pedagogía, 2018)
The present work describes the viewa of the author on what concerns the relations between the established power and the evaluation processes that are being followed in different countries in Europe and in South America, namely Brazil. The need for more transparency in the use of public funds is possibly the main reasson for the pressure the gouverments are putting over the universities, imposing or suggesting institutional and/or thematic evaluation procedures. The Portuguese experience is presented in detail, refering to the positive relations that presently exist between the governments and the institutions that represents the Portuguese universities.
Keywords: estructuras de poder; procesos de evaluación; Revista Española de Pedagogía